2002
DOI: 10.1146/annurev.immunol.20.100301.064812
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Natural Killer Cell Receptors: Multiple Molecular Solutions to Self, Nonself Discrimination

Abstract: In contrast to T cell receptors, signal transducing cell surface membrane molecules involved in the regulation of responses by cells of the innate immune system employ structures that are encoded in the genome rather than generated by somatic recombination and that recognize either classical MHC-I molecules or their structural relatives (such as MICA, RAE-1, or H-60). Considerable progress has recently been made in our understanding of molecular recognition by such molecules based on the determination of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
224
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(226 citation statements)
references
References 176 publications
1
224
0
1
Order By: Relevance
“…Ly49, NKR-P1, CD69, NKG2D and CD94/NKG2, the majority of them recognize classical MHC class I molecules (Ly49) or their structural relatives HLA-E (CD94/NKG2), MICA/B, RAE-1 or H-60 (NKG2D) and not carbohydrate ligands [39,40]. However, Fukuda and coworkers recently showed that NK cells lyse tumor cells via the sialyl-Lewis x carbohydrate determinant [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Ly49, NKR-P1, CD69, NKG2D and CD94/NKG2, the majority of them recognize classical MHC class I molecules (Ly49) or their structural relatives HLA-E (CD94/NKG2), MICA/B, RAE-1 or H-60 (NKG2D) and not carbohydrate ligands [39,40]. However, Fukuda and coworkers recently showed that NK cells lyse tumor cells via the sialyl-Lewis x carbohydrate determinant [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…LIR-1 is expressed on most or all monocytes, dendritic and B cells, and subsets of T cells and NK cells, where it functions as an inhibitory receptor by virtue of inhibitory motifs in its cytoplasmic tail and association with SHP-1, a tyrosine phosphatase that inhibits activating signals (15). Unlike the related killer inhibitory receptors (KIRs) on NK cells, which show allele-specific binding to class I MHC molecules (17), LIR-1 and its relative LIR-2 bind a broad range of classical and nonclassical class I MHC proteins (18,19). Structural and biochemical results suggest that LIR-1 uses a common binding interaction to recognize UL18 and class I MHC molecules, but it binds to UL18 with a Ͼ1,000-fold higher affinity (18).…”
mentioning
confidence: 99%
“…Three-dimensional structures of 2B4 were calculated on the basis of NOE data, slowly exchanging amide NH groups, chemical shift analysis, and 3 J NHα spin-spin coupling constants (see Experimental Procedures). The analysis of chemical shift index (CSI) (28), 3 J NHα (29), and short-range NOEs (30) is illustrated in Figure 1A and revealed at least nine β-strands and one short α-helix. The final three-dimensional structures of 2B4 derived from the NMR data are superimposed and illustrated in Figure 3A (atomic coordinates have been deposited in the RSCB Protein Databank).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, cells with abnormal MHC class I expression become targets of NK lytic activity that results from loss of inhibition of NK cell activation. Inhibitory receptors specific for MHC class I include the killer immunoglobulinlike receptors (KIRs), members of the Ly49 family, and the CD94/NKG2D family (3). Activating receptors include 2B4, CD16, CD44, CD69, NKR-P1, NKp30, NKp44, and NKp46 (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation